The balance of sleep: Role of the vestibular sensory system. (December 2018) - Besnard, Stephane; Tighilet, Brahim; Chabbert, Christian; Hitier, Martin; Toulouse, Joseph; Le Gall, Anne; Machado, Marie-Laure; Smith, Paul F.
Summary: The vestibular system encodes linear and angular head motion supporting numerous functions from gaze stabilization and postural control, to high-level cortical functions involving spatial cognition, including self-body perception, verticality perception, orientation, navigation and spatial memory. At the brainstem and mesencephalic levels, the vestibular organs also influence postural blood pressure regulation, bone density and muscle composition via specific vestibulo-sympathetic efferences and have been shown to act as a powerful synchronizer of circadian rhythms. Here, we review the evidence that sleep deprivation and sleep apnea syndrome alter vestibular-related oculo-motor and postural control, and that, in turn, vestibular pathologies induce sleep disturbances. We suggest that sleep-related neuroplasticity might serve the adaptation and compensation processes following vestibular lesions in patients. Interestingly, a reciprocal neuroanatomical route between the vestibular nuclei and the orexinergic neurons has been reported. While orexinergic modulation of the vestibular nuclei related to postural control has been suggested, we postulate that vestibular inputs might in turn influence the sleep-wake state switch, informing the brain about the daily quantity of motion.